Prosocial behaviour in South African students a qualitative enquiry - Cholerton, Steven M (Rhodes University, Faculty of Humanities, Department of Psychology, 1995)
The central aim of this study was to conduct a qualitative exploration of the prosocial inclinations possessed by young South African students. The literature review argues that traditional approaches to moral responding separate the individual from the social. An alternative approach that reinstates language and ideology is delineated. It is argued that such a paradigm is most appropriate to a study of prosocial responding during a period of social change. Hypothetical moral dilemmas were administered to twenty-nine students. Six students were selected and each was interviewed on two separate occasions. In this way six case studies were developed. The methodological traditions of phenomenology and hermeneutics were employed to analyze the protocols and subsequent interviews. Seven themes descriptive of a moral response were identified. These consisted of moral reasoning, empathy, mood, guilt, alienation, a sense of group-identity, and ambiguity regarding the relative interests of self versus other. These themes are fully discussed in terms of the literature. It is concluded that moral reasoning may be insufficient to motivate prosocial behaviour. Conventional moral narratives may be appropriated in order to make sense of conflicting emotions. Empathy was identified as a necessary but not sufficient condition for a prosocial response. Empathy might translate into either sympathy or personal distress. Mood was found to largely dictate attentional focus. Alienation was found to be a defensive formulation that inhibits the emergence of sympathy. Guilt might precipitate an alienated posture. It was found that guilt might be attributed to group-identity and thereby denied. Tension between a self- and other-oriented response, or between blame and sympathy, was common. It is suggested that this ambiguity reflects ideological contradictions that have been internalized. It is postulated that during periods of social change such contradictions are accentuated.
Keywords: Helping behavior; Interpersonal relations; Altruism; Social ethics; College students -- South Africa -- Attitudes